THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON COMPANY PERFORMANCE : CASE STUDY OF SMES IN KLAMBIR LIMA - Pramono, Cahyo; Wardani, Neng Sri; Syahputri, Chairunnisa (PT. Altin Riset Publishing, 2024)
This study aims to analyze the influence of financial literacy and financial inclusion on the performance of Small and Medium Enterprises (SMEs) in Klambir Lima. This research employs a quantitative approach using a survey method involving 100 SMEs as the sample. Primary data were collected through questionnaires covering aspects of financial literacy, financial inclusion, and company performance, while secondary data were obtained from SME financial reports and other official documents. Descriptive analysis results indicate that the level of financial literacy among SME owners and managers is moderate, with an average score of 3.4 on a Likert scale of 5 points. Financial inclusion is also at a moderate level with an average score of 3.6. Multiple linear regression analysis shows that financial literacy (β = 0.45, p < 0.05) and financial inclusion (β = 0.35, p < 0.05) have a significant impact on company performance, with the resulting regression model having an R-squared of 0.56. This study concludes that financial literacy and financial inclusion significantly affect the performance of SMEs in Klambir Lima. SME owners and managers who have a good understanding of finance and access to formal financial services can make better financial decisions, manage risks more effectively, and improve company performance. This study suggests the need for comprehensive financial education programs and policies that support financial inclusion to help SMEs optimize their potential and achieve greater success.